Prevalence of anatomical variables in mandibular canal anatomy: study using cone beam technology - López Videla-Montaño, Jorge; Vergara-Miranda, Martín; Rudolph-Rojas, Mauricio; Guzmán-Zuluaga, Carmen Lucía (Revista Facultad de Odontología Universidad de Antioquia, 2010)
Introduction: the purpose of this study was to evaluate the presence of a bifid mandibular canal variable (BMCV), by subject and by side. It was distributed by type, as classified by Naitoh, Hiraiwa, Aimiya and Ariji, adding the triple canal type. It was also associated with gender and the BMCV observation was compared with the panoramic view and the sagittal and coronal Cone Beam System. Methods: a random sample of 84 subjects (52 women, 32 men) between 12 and 80 years of age was analyzed; it was conducted between 2008 and 2009 at the Maxillo Facial Radiology Systems Center of Santiago de Chile. Volumetric acquisitions were made by CT, Cone Beam System, using Siemens Sirona equipment, model Galileos Comfort. Patients were classified by age and gender. We performed a qualitative and quantitative analysis both marking the path of the mandibular canal; BMCV was classified according to the classification of Naitoh, Hiraiwa, Aimiya and Ariji. The presence of BMCV was observed and compared between panoramic, and the sagittal and coronal slices. Results: 69% of the sample of the study showed at least one variation in the trajectory of the inferior dental canal. The variable of the trajectory of the dental canal which showed the highest frequency was the one classified as anterior elongation with confluence (39.28%) and, in second place the variable known as retromolar canal (23.80%). There was a statistical significant difference when the sagittal slices were compared with the coronal slices of the volumetric study through high resolution tomography in relation with the panoramic reconstruction, which suggests that the panoramic images are not sufficient to look for variables in the trajectory of the inferior dental canal. As it relates to gender, it was found that there was a statistically significant difference (p = 0.02) for the variable classified as lingual canal. Conclusions: Cone Beam System is critical to search the high frequency of BMCV, improving the diagnosis and prognosis of clinical and surgical procedures in the retromolar and posterior mandibular area.